PERAN PARTAI POLITIK KOALISI DALAM KEMENANGAN PASANGAN CALON NOMOR URUT 2 BUPATI DAN WAKIL BUPATI PADA PILKADA SERENTAK TAHUN 2020 DI KABUPATEN ROKAN HULU - Asrol Fickri; Ali Yusri (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2023)
ABSTRACT This thesis discusses the application of the function of coalition political parties to the winning of candidate pairs in the 2020 Pilkada in Rokan Hulu Regency. This coalition party was formed in the candidate pair No. Order 2 Sukiman-Indra Gunawan. Within the coalition party there are six political parties with 26 out of 45 seats or 60% of the seats for members of the Rokan Hulu DPRD. With this, the 20% parliamentary seat threshold has been crossed with the supporting parties, namely the Gerindra party, the Democrat Party, PKS, PDI-Perjuangan, Nasdem Party, and Hanura Party. The problem in this study is that the role of coalition political parties is not directly proportional to the victory obtained in the legislative election against the victory in the 2020 Rokan Hulu regional election, which was only a difference of 0.92%. This study aims to analyze the role of coalition political parties in the victory of pair No. Order 2 Sukiman-Indra Gunawan in the 2020 simultaneous local elections in Rokan Hulu Regency. This research approach is qualitative with descriptive research type. The research locations are in Rokan Hulu Regency, the Rokan Hulu Regency KPU Office, the Rokan Hulu DPRD, and also the Rokan Hulu Maju Coalition Team. Data collection using interview and documentation techniques. Data analysis techniques using qualitative analysis techniques. Researchers use Miriam Budiarjo's theory (2008) regarding the function of political parties in a democratic country, namely as political socialization, political recruitment, political communication, and a means of regulating conflict. The results of this study are that the role of coalition political parties in winning candidate pair No. Sort 2 Sukiman-Indra Gunawan was successfully carried out by going through the process and stages of carrying out this role. Coalition political parties use political socialization towards society, as well as political recruitment by political parties in determining the candidates they carry. Not only that, the coalition political parties also implemented political communication by carrying out political campaigns and also succeeded in suppressing conflicts that existed in society both during the regional elections and after the regional elections. Keywords: pilbup, the political coalition, prospective spouse